PEMENDAKAN SESUHUNAN PURA DALEM SUSUNAN WADON PADA SAAT PUJAWALI DI PURA DALEM SAKENAN DESA SERANGAN DENPASAR SELATAN - Wirawan, Anak Agung Ngurah (Pangkaja: Jurnal Agama Hindu, 2025)
Understanding the diversity of functions of temples along with the various rituals and ceremonies that differ across regions, as well as the uniqueness of specific ceremonies within temples, fosters an appreciation for this valuable cultural heritage and highlights its significant role in Balinese society. The diversity of functions and the uniqueness of ceremonial processes in temples are exemplified by distinctive rituals, one of which occurs in religious practices. For instance, the pujawali tradition at Dalem Susunan Wadon Temple in Desa Serangan is conducted every six months, coinciding with the sacred day of Kuningan. Additionally, each ceremony requires the manifestation of the deity residing in Dalem Susunan Wadon Temple prior to the execution of the pengerebegan ceremony; without this manifestation, the ceremony cannot take place. From this description, several research questions arise: Why is the manifestation conducted during pujawali at Dalem Sakenan Temple towards Dalem Susunan Wadon Temple? What is the process of this manifestation? What implications arise from its execution? These questions will be addressed through various theoretical frameworks: religious system theory will inform the first issue, structural-functional theory will address the second, and symbolic theory will serve as the basis for the third. The examination will broadly include the historical context of Dalem Sakenan Temple and Dalem Susunan Wadon Temple, the reasons for the manifestation of Sesuhunan at Dalem Susunan Wadon Temple during pujawali at Dalem Sakenan Temple, the methodology of the manifestation, the traditions associated with it, the process of manifestation, the materials involved, the procedural aspects, the requirements and timing of the manifestation, the parties involved, and the various implications of this ritual, encompassing theological, social, ethical, religious, and aesthetic dimensions.